Assessment of Molecular Residual Disease Using Circulating Tumor DNA to Identify Multiple Myeloma Patients at High Risk of Relapse - Dhakal, Binod; Sharma, Shruti; Balcioglu, Mustafa; Shchegrova, Svetlana; Malhotra, Meenakshi; Zimmermann, Bernhard; Billings, Paul R.; Harrington, Alexandra; Sethi, Himanshu; Aleshin, Alexey; Hari, Parameswaran N. (Frontiers in Oncology, 2022)
Background: Despite treatment with high-dose chemotherapy followed by autologous stem cell transplantation (AHCT), patients with multiple myeloma (MM) invariably relapse. Molecular residual disease (MRD)-negativity post-AHCT has emerged as an important prognostic marker predicting the duration of remission. Current techniques for MRD assessment involve bone marrow (BM) aspirate sampling, which is invasive, subject to sample variability, and limited by spatial heterogeneity. We compared the performance of a non-invasive, circulating tumor DNA (ctDNA)-based MRD assay with multiparameter flow cytometry (MFC) of marrow aspirate to predict relapse in AHCT recipients with MM. Methods: MRD assessment using ctDNA was retrospectively analyzed on 80 plasma samples collected at different time points from 28 patients, post-AHCT. MFC was used to assess the MRD from the BM biopsy. Individual archived BM aspirate slides or formalin-fixed paraffin-embedded slides from the time of MM diagnosis and matched blood were used to assess MRD at 3 months post-AHCT using a personalized, tumor-informed ctDNA assay. Results: ctDNA was detectable in 70.8% (17/24) of pre-AHCT patients and in 53.6% (15/28) of post-AHCT patients (3-month time point). Of the 15 post-AHCT ctDNA-positive patients, 14 relapsed on follow-up. The median PFS for ctDNA-positive patients was 31 months, and for ctDNA-negative patients was 84 months (HR: 5.6; 95%CI: 1.8-17;p=0.0003). No significant difference in PFS was observed in patients stratified by MFC-based MRD status (HR 1.2; 95%CI: 0.3-3.4;p=0.73). The positive predictive value for ctDNA was also significantly higher than MFC (93.3% vs. 68.4%). Conclusions: This study demonstrates tumor-informed ctDNA analysis is strongly predictive of MM relapse.